Cadmium induced modification of sugar accumulation and translocation along sweet sorghum stem - Tra, Dinh Thi Thanh; Hua, Xiao; Mengyuan, Zheng; Lubing, Wang; Feng, Luo; Yasuo, Igarashi; Changzheng, Xu (Vietnam Journal of Science and Technology, 2016)
Sweet sorghum has become a candidate species for combining phytoremediation with biofuel production due to heavy metal resistance, great biomass and sugar enrichment in stem. However, the influence of heavy metals on sugar accumulation in sweet sorghum is still unknown. In this study, Cd induced modification of sugar storage and translocation in stem was monitored using two sweet sorghum cultivars Keller (KE) and E-tian (ET). Brix degree, which represents sugar content in stem juice, displays significant reduction in response to exogenous Cd treatment in both lines. The sugar enrichment is more obviously repressed in the lower internodes while it is hardly affected in the top internodes. Excessive Cd results in drastically enhanced Cd accumulation, preferentially in the lower internodes. More interestingly, negative correlation between Cd and sugar content is detected along internodes, indicating antagonistic translocation between Cd and sugar along stem of sweet sorghum. The preferential compartmentation of Cd and sugar in different regions of stem provides novel insights into understanding and application of sweet sorghum for combining biofuel production with phytoremediation of heavy metal in soil.